'It's a-me, Mario!' Exploring dynamic changes and similarities in the composition of early Nintendo video game music. Issue 1 (January 2016) - Fox, James Anthony
Abstract : As with films, a thoughtfully composed video game soundtrack has the ability to dramatically enhance and elevate the experience for the audience or player. This article explores the potential issues and difficulties of composing for video game systems by studying the sound-producing hardware and music for two popular systems from one manufacturer. By comparing two of Nintendo's Super Mario titles, which appeared on both 8-bit and 16-bit systems, through an analysis of the technology, audio, visual (audiovisual), music, and gameplay elements, it is shown that the musical composition was affected by the limitations of processing power. The discussion shows how the composer, Koji Kondo, overcame the issues of limited computing power by using layers of repetition while applying various functions of music for film to enhance player immersion. Kondo composed theme music that has become engrained in popular culture and is synonymous with one of Nintendo's flagship franchises (Greening, 2014). By attempting to understand the method or approach behind the composition for earlier systems, it is possible to investigate and discuss the evolution of video game music while acknowledging and contributing to the study of music for games. A musical analysis of the Castle and Underwater themes on each system allows for a direct comparison of the compositional approach, while an audiovisual analysis reveals the presence of existing cinematic tropes and identifies potential influences on the creation of effective musical soundtracks for video games. Applying audiovisual theory to games will require the use of existing literature from Lissa (1965), Gorbman (1987), Chion (1994) and Tagg (2004), along with the work of Collins (2005; 2007a; 2007b; 2008a; 2008b), which adapts and applies audiovisual analysis to video games.